Construction of metal-organic frameworks (MOFs) and highly luminescent Eu()-MOF for the detection of inorganic ions and antibiotics in aqueous medium - Li, Jing-Ming; Li, Rui; Li, Xia (CrystEngComm, 2018)
The hydrothermal reaction of Ln(NO 3 ) 3 ·6H 2 O with 2,3′-oxybis(benzoic acid) (2,3′-H 2 oba) and 1,10-phenanthroline (phen) afforded the metal-organic frameworks (Ln-MOFs), [Ln 2 (2,3′-oba) 3 (phen) 2 ] n (Ln = La 1 , Eu 2 , Gd 3 , and Tb 4 ). 1 possesses a 3D network with [La1O 7 N 2 ] and [La2O 7 N 2 ] polyhedra, and 2-4 exhibit similar 3D networks containing [Ln1O 7 N 2 ] and [Ln2O 6 N 2 ] polyhedra. These complexes are thermally stable in air and have high stability in water in a wide pH range (acidic pH = 3 and alkaline pH = 13 solutions). Notably, MOFs 2 and 4 display bright red and green emission with the high fluorescence quantum yields of 75.57% and 41.86%, respectively. The highly luminescent chemically stable Eu-MOF shows multi-responsive luminescence sensing functions to detect Fe 3+ , Cr 6+ , and metronidazole (MDZ) in aqueous medium even in acidic conditions (pH = 3) via a fluorescence quenching mechanism. Excess Fe 3+ , Cr 6+ , and antibiotics can cause environmental pollution and serious diseases; thus, their detection is very important. In addition, one of the important advantages of Eu-MOF is that this complex can be excited at a long excitation wavelength (352 nm), which is in the near-visible radiation region of 350 nm < λ ex < 420 nm, and is an important requirement for its applications. A series of Ln( iii ) complexes were synthesized. The highly luminescent chemically stable Eu-MOF shows multi-responsive luminescence sensing functions.